Understanding world Christianity : China - Chan, Kim-Kwong, 1958- (Minneapolis : Fortress Press, 2019)
"Accessible in tone and brief in length, Understanding World Christianity: China is the definitive introduction to Chinese Christianity in the decades since Mao Zedong's cultural revolution. It is ideal for students, mission leaders, and any others who wish to know how Christianity influences, and is influenced by, its modern Chinese context"--back cover.
Introduction -- Chronological -- Sociopolitical -- Denominational -- Geographical -- Biographical -- Theological.
Includes bibliographical references.
Keywords: Christianity -- China; Civilization -- Christian influences; Christianity; China -- Civilization -- Christian influences; China